On the difficulties in manufacturing of luffa fibers reinforced biocomposites and variations in their dynamic properties - (:unkn) unknown (German Acoustical Society (DEGA), 2016)
Defects and structural differences in raw bio materials such as luffa plant result in large scattering mechanical properties such as density, damping and elasticity modulus. There are difficulties during the manufacturing process of the composites reinforced by bio materials inherent to the nature of bio materials The major problems and restrictions encountered with the use of green luffa materials for composite manufacturing and the variations in the dynamic properties of luffa composites are studied in this study. First, the structural differences in the raw luffa plants are presented and the difficulties in manufacturing the luffa fibers based composites are discussed. After that, the variations in the measured modal parameters of luffa composites such as natural frequencies and loss factors are presented. The results showed that the luffa composites can be manufactured with similar properties without any special selection of luffa cylindrica samples for controlling the structural differences. However, a preliminary selection of bio raw samples is required if small variations in the dynamic hence mechanical properties of luffa composites are desired. © 2016, German Acoustical Society (DEGA). All rights reserved.
Keywords: Composite manufacturing; Dynamic properties: 72.7; Luffa bio composite